Strategi dan Taktik CSE Menghadapi Kasus Kandungan Pestisida Produk Coca-Cola di India tahun 2003-2006 - Bayu Prayoga, I Gusti Ngurah Agung; Fasisaka, Idin; Dewi, Putu Ratih Kumala (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
In August 2003, Public of India were shocked by an issue about pesticide residue in softdrink. CSE, Delhi-based ENGO reporting that alarming amount of pesticide cocktail was found in softdrink samples of Indian market. Majority of the samples was under Coca Cola India Company’s brands. In order to pressing the government to act, CSE using strategies and tactics that still in range of the organization resources. This study aims to describe the strategies and tactics of CSE in order to giving pressure to the government to act and make a regulation about this cause. This study will assessed using concepts of ENGO and ENGO strategies and tactics, with locus from 2003 to 2006 which is the time gap between first and second CSE report about this case. Kata Kunci: CSE, pestisida, strategi, taktik